EIF VC Survey 2023: Market sentiment, scale-up financing and human capital - Helmut Krämer-Eis; Annalisa Croce (European Investment Fund (EIF), 2023)
The EIF VC Survey and the EIF Private Equity Mid-Market Survey (the largest combined regular survey exercises among General Partners on a pan-European level) provide an opportunity to retrieve unique market insights. This publication is based on the results of the 2023 VC Survey, conducted by the EIF with the support of Invest Europe. The paper focuses on the market sentiment as well as on issues related to scale-up financing and EU strategic autonomy. The study looks at the current situation, developments in the recent past and expectations for the future. It highlights substantial challenges, but also opportunities as perceived by survey participants. The main results are summarised and compared over time. The publication provides a valuable picture of the developments in the VC market in 2023 as well as an outlook for the near future. The EIF Working Papers are designed to make available to a wider readership selected topics and studies in relation to EIF's business. The Working Papers are edited by EIF's Research & Market Analysis and are typically authored or co-authored by EIF staff or are written in cooperation with EIF.
Keywords: 330